Record harvests in the Sahel region - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The total cereal production of the nine countries of CILSS (Permanent Interstate Committee for Drought Control in the Sahel) is estimated at a record 10.6 million t for 1998, which is 31% higher than in 1997 and 17% above the average of the past...